2016
DOI: 10.1080/09650792.2016.1215930
|View full text |Cite
|
Sign up to set email alerts
|

‘We are more than EFL teachers – we are educators’: emancipating EFL student-teachers through photovoice

Abstract: The prevailing pedagogical orientations of EFL education in Spain oppress learners intellectually in ways that are counterproductive to their learning. As a reaction to this, 129 EFL student-teachers (STs) took part during the 2013-14, 2014-15, and 2015-16 academic years in a workshop which drew on the methodology of participatory action research and on photovoice as a data creating strategy, in order to emancipate these STs intellectually, boost their EFL development, and offer an alternative critical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The images students captured represented elements of the local community that the students found unexpected or surprising. It put the viewpoints of the students into the centre of the process (Villacañas de Castro, 2017). What was interesting was that the images students captured were often images that the instructors were not expecting the students to find unfamiliar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The images students captured represented elements of the local community that the students found unexpected or surprising. It put the viewpoints of the students into the centre of the process (Villacañas de Castro, 2017). What was interesting was that the images students captured were often images that the instructors were not expecting the students to find unfamiliar.…”
Section: Discussionmentioning
confidence: 99%
“…Participants take photographs of assigned themes and write descriptions to accompany their photos. Photovoice can have a pedagogical and a research purpose by supporting learning outcomes as well as inquiry in educational settings (Villacañas de Castro, 2017). In contexts with international students, examples of this approach include identifying international students’ food choices through students taking photographs of what they eat and then captioning those photographs during one week (Corcoran, 2018) and exploring international students’ adaptations to new academic and cultural experiences through rounds of photo taking (Q.Wang & Hannes, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this pre-service training literature we find a notable interest in identifying the potential of photo-elicitation-it has been used to investigate teachers' cognition, their theories, ideas, beliefs and values, providing knowledge that enables awareness and reflection, influencing their development or modification and, consequently, in decision-making in educational action Caielli et al, 2018;DiCicco, 2015;Graziano, 2011;Johnson & Smagorinsky, 2013;Mathews & Crew, 2016;McCartney & Harris, 2014;Sinclair & Thornton, 2018;Varea & Pang, 2018;White & Murray, 2016). Likewise, the teacher's understanding and thinking are enhanced through photo-elicitation, and several studies have reported that this technique has a positive impact on their professional identity (Allen & Labbo, 2001;Da Cunha et al, 2014;Mitchell et al, 2010;Salazar et al, 2016;Savva & Erakleous, 2018;Seow, 2016;Villacanas de Castro, 2017;White & Murray, 2016). This technique has been used in various subjects during pre-service teacher training, but most studies have focussed on Physical education and English (Da Cunha et al, 2014;Langdon et al, 2014;Legge & Smith, 2014;Sinclair & Thornton, 2018;Varea & Pang, 2018;Walker et al, 2017; for the second, Caielli et al, 2018;Dicicco, 2015;Graziano, 2011;Johnson & Smagorinsky, 2013;Villacanas de Castro, 2017;White & Murray, 2016), while two have dealt with photo-elicitation in social studies (Garrett & Matthews, 2014;Mathews & Crew, 2016).…”
Section: Photo-elicitation In the Pre-service Teacher Practicummentioning
confidence: 99%
“…Eight studies in this category were designed with the intention of using research to prepare preservice teachers for work in urban schools with racially diverse learners [16,23,24,27,40,49,80,97]. Others were designed to support groups of students such as English Learners who primarily spoke other languages [18,31,52,54,70,87] or low-socioeconomic-status rural students [64]. In some studies, the political dimensions of teaching were accessed through research involving caregivers.…”
Section: Political Facets Of Teachers' Researchmentioning
confidence: 99%